MACROZOOBENTOS COMMUNITIES COMPOSITION ON THE LONGITUDINAL PROFILE OF THE VOGOŠĆA RIVER - Omeragić, Amina; Gajević, Mahir (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Macrozoobenthos is a community of organisms that is a very important part of aquatic ecosystems looking at their role in the circulation of nutrients through food chains. The decline in water quality directly affects the composition and structure of macrozoobenthos, and is therefore a very good indicator of the state of aquatic ecosystems. The aim of this research is to analyze the composition and structure of the macrozoobenthos community of the Vogošća river on its longitudinal profile. Sampling of macrozoobenthos was performed in April 2019 at three sites. In the laboratory of the Faculty of Science in Sarajevo, isolation and identification of collected macrozoobenthos samples and analysis of macrozoobenthos communities were performed. Results show a high diversity of macrozoobenthos communities in the upper and middle part of the Vogošća river. The lower part of the stream is the poorest in diversity, which is the most polluted of all investigated sites.